2018
DOI: 10.1080/0092623x.2018.1474410
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Partner Status and Sexual Behavior on College Women’s Consent Communication and Feelings

Abstract: Sexual consent has permeated mainstream discourse as a mechanism used to decrease rates of sexual assault and increase sex-positive communication. Women's external consent behaviors are frequently examined; however, research exploring their internal consent and feelings associated with sexual activity are understudied. The purpose of this study was to understand how partner status and sexual behavior at most recent sexual activity influence women's external/internal consent and feelings during sexual activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
4
29
0
1
Order By: Relevance
“…That we did not corroborate previous findings regarding between-person sociodemographic variability of sexual consent may have been due to our sample comprising only people who were in committed sexual relationships. 2 Indeed, how people conceptualize sexual consent can vary based on relationship status (Humphreys & Brousseau, 2010;Orchowski et al, 2020;Righi et al, 2019), as can the ways they experience and communicate willingness to engage in sexual activity Marcantonio et al, 2018;Walsh et al, 2019). Because previous studies on the between-person variability of sexual consent collected data from samples that were much more heterogeneous than the present study regarding relational context, comparisons of between-person effects across studies must be done with caution.…”
Section: Discussionmentioning
confidence: 83%
“…That we did not corroborate previous findings regarding between-person sociodemographic variability of sexual consent may have been due to our sample comprising only people who were in committed sexual relationships. 2 Indeed, how people conceptualize sexual consent can vary based on relationship status (Humphreys & Brousseau, 2010;Orchowski et al, 2020;Righi et al, 2019), as can the ways they experience and communicate willingness to engage in sexual activity Marcantonio et al, 2018;Walsh et al, 2019). Because previous studies on the between-person variability of sexual consent collected data from samples that were much more heterogeneous than the present study regarding relational context, comparisons of between-person effects across studies must be done with caution.…”
Section: Discussionmentioning
confidence: 83%
“…This discrepant finding regarding gender may be due to women being more comfortable communicating consent via explicit verbal cues within a committed relationship than they would in other contexts. Indeed, Marcantonio et al (2018) found that women with serious partners reported greater use of initiator consent communication (e.g., explicit verbal cues) than women with casual or first-time partners-other types of external sexual consent may not be as variable across relationship types.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the relationship between partners influences how consent is conveyed. Women engaging in sexual acts with a serious dating partner were more likely to use nonverbal cues to convey consent compared to women engaging in sexual acts with less serious partners (Marcantonio et al , 2019). Such scripts could interfere with the application of AC policies.…”
Section: Relationship Between Victim and Offendermentioning
confidence: 99%